TRANSFORMATION OF COMMUNICATIONS LANGUAGE IN THE INTERNATIONAL LAW CONTEXT - Калитенко, І. О. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. Over time, any phenomenon is in one or another way experiencing its development, evolution, transformation. This is true with a transformation of the language of communication related to international law as a social and humanitarian phenomenon. The article examines the features and specifics of the general communicative tendencies that have manifested themselves in international law, primarily on the basis of legal texts – written communicative acts. This aspect of the study is chosen on the fact that legal communication, and today’s international law, in one way or another, are primarily implemented in the language of written communicative acts – international treaties, international conventions, acts of international organizations. The aim of the article is to investigate the boundaries of communicative development of contemporary international law in written and oral forms, to determine the correlation of general communicative tendencies with the corresponding stages of the formation of international law. The aim is determined by the following tasks: to consider the general peculiarities of development of the problem of communication in philosophy and, therefore, to determine the generalized changes that have occurred over time in international legal practice in the context of its sectoral communication. The research methodology consists of socio-cultural, structural-functional and comparative-historical approaches. Research results. In international law, there is a certain set of consistent vocabulary that applies in writing (international treaties, international conventions, acts of international organizations) and oral forms, where acts of interaction between states are based on the international legal tradition, which subjects of international law are recognized as a legal norm, or on the basis of general principles of law, which are understood by participants in intergovernmental relations as a "basis of the basis", and therefore do not require a separate discussion. Each of the historical periods of the formation of communication from ancient times to the present left its clear imprint on the nature of relations between states. Today’s international law operates in the language that was formed after the adoption of the UN Charter and a large number of international legal instruments – treaties, conventions, acts of international organizations. The international relations usually speak the terminology of the documents mentioned above, since in their relations the states rely on their written communicative acts, and the oral form of international communication is based on it, in international legal acts on all areas of international legal practice. Discussion. International law is a "sub-branch" of the legal spiritual being, in which throughout its history used as a characteristic in general for human communication communicative means, and communicative acts that are characterized by international law, in which, over time, the adoption of a universal language for all subjects of international law was carried out, the development of which was, historically, due to the general history of mankind. Conclusion. Summarizing all above, we have grounds to state that international law, as one of the spheres of human communication, was a reflection of those communicative processes that have taken place with humanity throughout its history. As the example of the general changes that have taken place in the field of international law, we can also observe communicative tendencies of a particular historical epoch that directly affect the nature of communications within international law